NQR as a target for new antibiotics - González-Montalvo, Martín A.; Sorescu, Jennifer M.; Yuan, Ming; DePaolo-Boisvert, Joseph; Liang, Pingdong; Juárez, Oscar X.; Tuz, Karina (Frontiers in Microbiology, 2025)
The rise in antimicrobial resistance has underscored the urgent need for identification of novel targets against antibiotic resistant bacteria, which pose enormous threats to public health. The respiratory enzyme NQR carries essential roles in pathogenic bacteria, producing an ion gradient across the plasma membrane that drives ATP generation by the oxidative phosphorylation system. The vital role of NQR in a multitude of pathogenic microbes for which drug development is a high priority, such as Vibrio cholerae, Chlamydia trachomatis, and Pseudomonas aeruginosa, makes it an ideal drug target meriting investigation, especially since this enzyme is absent in human cells. A diverse array of NQR inhibitors have previously been identified, ranging from the ubiquinone analogs korormicin, HQNO, and aurachin D-42, which occupy one of two ubiquinone binding sites, to monovalent and divalent cations such as Ag+ and Zn2+ that react with SH groups. To overcome cytotoxicity associated with many established NQR inhibitors, drug development efforts have produced synthetic analogs of korormicin that exhibit minimal toxicity. To address the urgent need for alternative treatments, our group has explored the repurposing of FDA-approved drugs with established safety profiles as NQR inhibitors. Our recent work revealed that clofazimine, and FDA-approved orphan drug, is as a potent NQR inhibitor with strong antivirulence properties. This review highlights the role and significance of NQR and its inhibitors, with an emphasis on the potential development of antibiotics to target this respiratory enzyme.